Distinctive Features of Composition and Properties of Heavy Naphthenic-Aromatic Oil and Options for its Proficient Refining - Antonov, S. A.; Matveeva, A. I.; Pronchenkov, I. A.; Bratko, R. V.; Nikulshin, P. A.; Kilyakova, A. Yu; Gerasimov, A. V. (Chemistry and technology of fuels and oils, 2022)
The article examines the chemical composition and physicochemical properties of heavy naphthenic-aromatic oil and its fractions. In comparison with mixtures of West Siberian and Samara oils, the naphthenic-aromatic heavy oil is distinguished by higher viscosity and density, which is associated with high content of resinous-asphaltenic compounds and absence of gasoline fractions. The diesel fraction is distinguished by good low-temperature characteristics and contains a large quantity of aromatic hydrocarbons represented primarily by monocyclic structures. The lube oil fractions also have good low-temperature characteristics, but are characterized by low viscosity index, which stems from high content of polycyclic naphthenic hydrocarbons with short alkyl chains. The vacuum residue consists primarily of resinous matters and has a high content of metals (nickel, vanadium, etc.). A scheme of heavy oil refining is proposed for getting unique high-quality products, such as low-pour-point fuels, oil-based drilling fluids, naphthenic oils of various viscosities, high-quality asphalt and coke, and nickel and vanadium concentrate.